Research Progress and Application of Prokaryotic Laccase - Xin ZHANG; Gongliang LIU; Weidong BAI; Jinglong LIANG; Rui LIU (Shipin gongye ke-ji, 2023)
A variety of phenolic and non-phenolic substrates can be oxidized by laccase using molecular oxygen as an auxiliary substrate. Due to the fact that laccase produces only water as a by-product, laccase is considered a "green tool enzyme" because it is environmentally friendly. Among the many industries in which laccase is used are sewage treatment, paper making, textiles, food, organic synthesis, biopharmaceuticals, detection, and ecological restoration. Compared to fungal laccase, prokaryotic laccase tends to have the following advantages: higher thermal stability and higher optimum reaction temperature, better suited to catalyse reactions under alkaline conditions, less sensitive and less dependent on inhibitors and metal ions, and more amenable to heterologous expression and protein engineering transformation. As a result, prokaryotic laccase has gained increasing attention in recent years. It describes in detail the origins, structure, catalytic process and physicochemical properties of prokaryotic laccase, its applications, and the recent research progress in this area over the past few years.